2011
DOI: 10.1557/opl.2011.924
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Of Indigo Molecules Inside The Palygorskite Clay Channels

Abstract: The search for durable dyes led several past civilizations to develop artificial pigments. Maya Blue (MB), manufactured in pre-Columbian Mesoamerica, is one of the best known examples of an organic-inorganic hybrid material. Its durability is due to the unique association of indigo molecule and palygorskite, a particular fibrous clay occurring in Yucatan. Despite 50 years of sustained interest, the microscopic structure of MB and its relation to the durability remain open questions. Combining new thermogravime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Of particular interest herein are reports showing that external surfaces of sepiolite and palygorskite were 2.3-3.8 × 10 5 and 1.4-1.9 × 10 5 m 2 kg −1 , respectively [9]. Acid digestion experiments also showed larger tunnels for sepiolite, thus allowing for greater diffusion rates [10][11][12][13].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Of particular interest herein are reports showing that external surfaces of sepiolite and palygorskite were 2.3-3.8 × 10 5 and 1.4-1.9 × 10 5 m 2 kg −1 , respectively [9]. Acid digestion experiments also showed larger tunnels for sepiolite, thus allowing for greater diffusion rates [10][11][12][13].…”
Section: Introductionmentioning
confidence: 89%
“…These observations further confirmed specific adsorption mechanisms allowing for charge transfer between the pink complex and siloxane groups and, like for LP inhibition, the total number of surface sites did not account for adsorption of the pink complex available. Furthermore, additional considerations showed that the relative effectiveness of palygorskite vs sepiolite for inhibiting LP were not accounted for by specific surface area (105 vs 308 m 2 g −1 ; [6,7]), width of channels (0.37 × 0.64 nm vs 0.37 × 1.06 nm; [8]), density of external surfaces (1.4-1.9 × 10 5 vs 2.3-3.8 × 10 5 m 2 kg −1 ; [9]), or diffusion rates [10][11][12][13] either.…”
Section: Lipid Peroxidationmentioning
confidence: 99%
“…This dehydroindigo (or, better, the multiorganic component) model, although accepted by several groups, ,,, has not been considered or only partially accepted in much of recent literature, , retaining the idea that indigo is the unique organic component in the MB, in the following, the “all-indigo” model. The focus in the dehydroindigo model has been made on the presence of other dyes accompanying indigo in MB; although HPLC/MS experiments on MB extracts permitted to characterize unambiguously the presence of dehydroindigo, isatin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Tunnels have been recognized as an important parameter determining the transfer to and from solutes. Sepiolite owns a higher number of adsorption sites than palygorskite (Table 1A; [4]), along with larger tunnels, allowing for greater diffusion rates [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%